2014
DOI: 10.1142/s0219887814500637
|View full text |Cite
|
Sign up to set email alerts
|

A vertical Liouville subfoliation on the cotangent bundle of a Cartan space and some related structures

Abstract: In this paper we study some problems related to a vertical Liouville distribution (called vertical Liouville-Hamilton distribution) on the cotangent bundle of a Cartan space. We study the existence of some linear connections of Vrȃnceanu type on Cartan spaces related to some foliated structures. Also, we identify a certain (n, 2n − 1)codimensional subfoliation (F V , F C * ) on T * M 0 given by vertical foliation F V and the line foliation F C * spanned by the vertical Liouville-Hamilton vector field C * and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The vertical Liouville distribution on the tangent bundle of a (pseudo) Finsler space was defined for the first time in [3] where some aspects of the geometry of the vertical bundle are derived via vertical Liouville distribution. A similar study on the cotangent bundle of a Cartan space can be found in [9]. Also, other signifiant studies concerning the interrelations between natural foliations defined by Liouville fields on the tangent bundle of a Finsler space and the geometry of the Finsler space itself, as well as similar problems on Cartan spaces are intensively studied in [5] and [1], respectively.…”
Section: 1 Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The vertical Liouville distribution on the tangent bundle of a (pseudo) Finsler space was defined for the first time in [3] where some aspects of the geometry of the vertical bundle are derived via vertical Liouville distribution. A similar study on the cotangent bundle of a Cartan space can be found in [9]. Also, other signifiant studies concerning the interrelations between natural foliations defined by Liouville fields on the tangent bundle of a Finsler space and the geometry of the Finsler space itself, as well as similar problems on Cartan spaces are intensively studied in [5] and [1], respectively.…”
Section: 1 Introductionmentioning
confidence: 83%
“…Also, other signifiant studies concerning the interrelations between natural foliations defined by Liouville fields on the tangent bundle of a Finsler space and the geometry of the Finsler space itself, as well as similar problems on Cartan spaces are intensively studied in [5] and [1], respectively. See also [9,11,16,17].…”
Section: 1 Introductionmentioning
confidence: 99%
“…where the local components are expressed by Proof. Follows using an argument similar to that used in [4,22]. It can be found in [23] for a more general case when the manifold M is endowed with a Finsler structure.…”
Section: An Almost Contact Structure On the Vertical Liouville Distrimentioning
confidence: 95%
“…The paper is organized as follows. In the first section we present the preliminary results on the cotangent bundle (see for instance [13,[19][20][21]28]). Also, we study the tension and the strong torsion of the nonlinear connection and investigate the homogeneous case.…”
Section: Introductionmentioning
confidence: 99%
“…show us the relation between the Jacobi endomorphism given by(13) and curvature tensor from(2).We recall that the pair (T * M, ω) is a symplectic manifold. Every differentiable function f : T * M → R determines an unique vector field X f on T * M called the 1650071-7 Int.…”
mentioning
confidence: 99%